Characterizations of Capsule Closure in Hip Arthroscopy Are Infrequently and Incompletely Reported: A Systematic Review - John J. Heifner, M.D; Leah M. Keller, D.O; Gagan Grewal, M.D; Ty A. Davis, D.O; Jonathan Brutti, B.S; Jan Pieter Hommen, M.D (Elsevier, 2024)
Purpose: To review the recent literature to provide an updated characterization of capsule closure techniques in hip arthroscopy and to determine if the characteristics of closure impacted clinical outcomes. Methods: In keeping with the Preferred Reporting in Systematic Reviews and Meta Analyses (PRISMA) guidelines, a systematic review was performed with the following eligibility criteria: patients over 18 years of age who underwent primary hip arthroscopy with reporting of patient reported outcome measures or revision/failure, and a sufficiently detailed description of capsule closure. The GRADE framework evaluated study quality, and ROBINS-I evaluated the risk of bias. Results: Across 18 studies (N = 3277) an interportal capsulotomy was reported in 12 studies (1972/3277) cases, and a T-type capsulotomy was reported in six studies (1305/3277) cases). Six studies reported using #2 suture. Nonabsorbable suture was reported in six studies, and absorbable suture in six studies. The rate of failure was 10.5% across five studies (N = 1133) and the rate of revision was 4.4% across 13 studies (N = 2957). Conclusions: Capsule closure is commonly performed with #2 high strength suture-the T-type using two to three sutures in the vertical limb and two to three in the transverse limb, and the interportal type using two to three sutures. Compared to earlier reports, there is a trend for increased utilization of T-type capsulotomy. Although there is a growing body of investigations into the efficacy of routine capsule closure following hip arthroscopy, our results demonstrate infrequent and inconsistent reporting of capsule closure characteristics. Level of Evidence: Level IV, systematic review of Level I-IV studies.